Pengaruh Model Pembelajaran Quantum Teaching Terhadap Motivasi Belajar Siswa Kelas Vlll SMP Negeri 2 Siborongborong Kecamatan Siborongborong Kabupaten Tapanuli Utara Tahun Pembelajaran 2022/2023 - Dina Infantri Aritonang; Dorlan Naibaho; Boho P. Pardede (Journal of Creative Student Research, 2023)
The aim of this research is to determine the influence of the Quantum Teaching Learning Model on the Christian Religious Education Learning Motivation and Characteristics of Class VIII Students of SMP Negeri 2 Siborongborong 2022/2023. The method used in this research is the Descriptive Inferential Quantitative research method. The population is all 222 students of class VIII of SMP Negeri 2 Siborongborong who are Christians. Sampling used purposive sampling technique, namely class VIII 1 with a total of 32 people. Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant influence of the Quantum Teaching Learning Model on the PAK Learning Motivation and Characteristics of class VIII students at SMP Negeri 2 Siborongborong This research concludes that there is a positive and significant influence of the Quantum Teaching Learning Model on the PAK Learning Motivation and Characteristics of Class VIII Students of SMP Negeri 2 Siborongborong 2022/2023 amounting to 45.69%. In connection with the results of this research, the author provides input for schools to improve and maintain a good and structured quantum teaching learning model so that it can increase student learning motivation.